ASME 2012 Third International Conference on Micro/Nanoscale Heat and Mass Transfer 2012
DOI: 10.1115/mnhmt2012-75136
|View full text |Cite
|
Sign up to set email alerts
|

Digital Microfluidic Device for Hotspot Cooling in ICS Using Electrowetting on Dielectric

Abstract: To meet the increasing demand of efficient cooling performance in small scale, this paper presents a digital microfluidics (DMF) microscale liquid cooling system which works on the principle of electrowetting on dielectric (EWOD). In EWOD DMF, fluids are handled drop-wise by external electric field. When the dispensed liquid droplet arrives at the hotspot by EWOD DMF operation, it picks up heat and removes heat when it leaves. This process can be repeated for a series of droplets by using a comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…This low-energy surface is also free from the hydrophobic polymer coating that behaves as an additional thermal barrier. However, DMF-based cooling studies [ 22 , 23 , 24 , 25 , 26 , 27 , 28 ] previously reported critically require the hydrophobic polymer coating on top of the hot spot to facilitate droplet transportation. As indicated in Figure 1 , while a cooling droplet passes over the target hot spot, the heat is rejected based on sensible heat transfer, which limits the level of applicable heat flux.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This low-energy surface is also free from the hydrophobic polymer coating that behaves as an additional thermal barrier. However, DMF-based cooling studies [ 22 , 23 , 24 , 25 , 26 , 27 , 28 ] previously reported critically require the hydrophobic polymer coating on top of the hot spot to facilitate droplet transportation. As indicated in Figure 1 , while a cooling droplet passes over the target hot spot, the heat is rejected based on sensible heat transfer, which limits the level of applicable heat flux.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, DMF has drawn attraction as a liquid-handling platform for effective cooling of target heating sources [ 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. Unlike conventional cooling technologies such as heat pipes [ 29 , 30 ], heat spreaders [ 31 , 32 ], microchannel-guided liquid cooling [ 33 , 34 ], and jet impingement cooling [ 35 ], DMF does not require additional mechanical components such as pumps, valves, microchannels, and capillary wick structures for coolant delivery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past 25 years, there has been a surge of interest in the field as researchers miniaturize traditional macro-scale processes to micro-dimensions, and explore new aspects of science previously unseen from a macro-scale vantage point. This technology has been used by studies in a range of applications, from clinical medicine and microbiology, to electronics and the oil industry (Hettiarachchi et al 2007;Gómez-sjöberg et al 2005;Bindiganavale et al 2012;Fadaei et al 2011). In comparison to their macro-scale counterparts, microfluidic processes have the following advantages: faster reaction times and better process-control; reduced waste generation and reagent consumption; system compactness and parallelization; and reduced cost and disposability.…”
Section: Emerging Arsenic Detection Researchmentioning
confidence: 99%
“…In the past 25 years, there has been a surge of interest in the field as researchers miniaturize traditional macro-scale processes to micro-dimensions, and explore new aspects of science previously unseen from a macro-scale vantage point. This technology has been used by studies in a range of applications, from clinical medicine and microbiology, to electronics and the oil industry (Hettiarachchi et al 2007;Gómez-sjöberg et al 2005;Bindiganavale et al 2012;Fadaei et al 2011). In comparison to their macro-scale counterparts, microfluidic processes have the following advantages: faster reaction times and better process-control; reduced waste generation and reagent consumption; system compactness and parallelization; and reduced cost and disposability.…”
Section: Emerging Arsenic Detection Researchmentioning
confidence: 99%